Improving the Teaching Quality of Elementary School Teachers through the Implementation of E-Education Based on the JIBAS Application - Afrilianti, Alviani Risti; Sianturi, Risbon; Kadarsah, Deni (International Conference on Elementary Education, 2024)
The efforts to improve the quality of learning carried out by elementary school teachers are not enough just to carry out certain directions and supervision, the implementation of which is very limited, but must also be supported by an evaluation system that can be monitored at any time by the Principal. Therefore, optimizing the use of JIBAS e-Education technology is expected to assist School Principals in carrying out supervision and providing input in improving the quality of learning. To determine the role of e-Education based on the JIBAS application in improving the quality of learning which is carried out by elementary school teachers, This research was designed by applying action research methods to elementary school teachers which included two research cycles. The results of this research found that implementing e-Education based on the JIBAS application can be carried out as long as the school is prepared for it. The school must ensure that the facilities and infrastructure are adequate and the school's human resource elements are able to use these technological devices. Through the implementation of this application, teacher’s mastery of material and skills in learning process has increased significantly. Thus, it can be concluded that the implementation of JIBAS e-education has a positive impact on improving the quality of elementary school teachers in the student learning process.